Entrepreneurial Finance, 7th Edition - J. Chris Leach; Ronald W. Melicher (Cengage Learning, 2020)
Master each step of the complete ""life cycle"" of a firm with Leach/Melicher's ENTREPRENEURIAL FINANCE, 7E. This edition vividly explains the theories, corporate finance tools and techniques you need to start, build and eventually harvest a successful entrepreneurial venture today. Using an inviting presentation, this book emphasizes sound financial management practices as you learn how to secure financing, use business cash flow models and strategically position your early-stage company. You also learn how to interact effectively with financial institutions and regulatory agencies that can impact venture growth and ensure liquidity for investors. Updates throughout this edition feature real examples as well as in-depth capstone cases and mini-cases drawn from actual entrepreneurial ventures and common financial scenarios. Strengthen your entrepreneurial skills as you study key concepts, such as venture capital funds, clean tech, sustainable sales growth, strategic alliances, licensing agreements and exit strategies. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.